IMPROVING THE FUNCTION OF PERSONAL COMPUTER EQUIPMENT AS A TOOL CONTROL HOUSE - Soejianto Soejianto; Ir. Rafael A. Gafar (Jurnal Sistem Komputer, 1992)
Tool made in this thesis allows a personal computer connected to an interface or other equipment to control home equipment. Function circuit using infra-red radiation to carry data between personal computers and control devices (slave). Application of this tool is in the operations control system and receiving information from a variety of equipment scattered around the house, factory or office.